Review on Leader Member Exchange Theory: Supply Chain Management to Increase Efficiency - Moses Glorino Rumambo Pandin; Mohamad Iqbal Arrasyid; Amaliyah Amaliyah (International Journal of Supply Chain Management, 2019)
This study aims to examines three elements shape leadership in Leader-Member Exchange (LMX) theory as a relationship and process. The goal of supply-chain management is to create a satisfied customer by coordinating all of the activities of the supply-chain members into a seamless process. Â LMX quality is important for the company, because it relates to employee behavior and attitudes, including improving employee performance. The research method applied literature review using description logic and systematics. In this article the theory will be observed specially the effect of LMX on employee performance and antecedents of LMX. The results of the study found that the effect of LMX quality on performance is determined by the characteristics of the task as antecedent LMX in the company.